Coronavirus - SARS- CoV-2 - infection prevention - own experience - Marzena Danielak; Piotr Dziemidok (Medycyna Ogólna i Nauki o Zdrowiu, 2021)
Introduction In December 2019, an epidemic of infections caused by a new beta-coronavirus called SARS CoV-2 (Severe Acute Respiratory Virus Corona-2) broke out in the Chinese city of Wuhan. According to modern taxonomy, the species SARS Cov-2 belongs to the order – Nidovirales, family – Coronaviridae, subfamily – Coronavirinae, Genus – Betacoronavirus, lineage – Sarbecovirus. The World Health Organization (WHO) named the disease caused by the SARS CoV-2 COVID-19 virus (Coronavirus disease) on 11 February, 2020. On 11 March, 2020, after the epidemic had spread to all continents, the World Health Organization declared the COVID-19 pandemic. SARS CoV-2 virus is transmitted by airborne droplets, as well as through contaminated surfaces and objects. The presence of the virus has been shown in the body fluids of infected people, such as nasal and throat secretions, tears, sputum, stool and blood. The incubation period is 5 to 14 days. Non-specific prophylaxis is important in reducing the number of infections caused by SARS CoV-2 virus.